History, philosophy, and value of mechanical models in sports science and engineering - Senner, V. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
This article is giving an introduction to JSET`s special section on mechanical models. It explains why mechanical models represent essential tools in sports engineering, defines their potential application fields and proposes a possible categorization. Further two short examples of mechanical models with corresponding literature and an overview of the manuscripts included in this special section are given.